Kinase domain activation through gene rearrangement in multiple myeloma. Issue 11 (November 2018) - Morgan, Gareth; He, Jie; Tytarenko, Ruslana; Patel, Purvi; Stephens, Owen; Zhong, Shan; Deshpande, Shayu; Bauer, Michael; Weinhold, Niels; Schinke, Carolina; Rasche, Leo; Bailey, Mark; et al.
Abstract Chromosomal rearrangements that result in oncogenic kinase activation are present in many solid and hematological malignancies, but none have been reported in multiple myeloma (MM). Here we analyzed 1421 samples from 958 myeloma patients using a targeted assay and detected fusion genes in 1.5% of patients. These fusion genes were in-frame and the majority of them contained kinase domains from either receptor tyrosine kinases (ALK, ROS1, NTRK3, andFGFR1 ) or cytoplasmic kinases (BRAF, MAP3K14, andMAPK14 ), which would result in the activation of MEK/ERK, NF-κB, or inflammatory signaling pathways. Fusion genes were present in smoldering MM, newly diagnosed MM, and relapse patient samples indicating they are not solely late events. Most fusion genes were subclonal in nature, but oneEML4-ALK fusion was clonal indicating it is a driver of disease pathogenesis. Samples with fusions of receptor tyrosine kinases were not found in conjunction with clonal Ras/Raf mutations indicating a parallel mechanism of MEK/ERK pathway activation. Fusion genes involvingMAP3K14 (NIK ), which regulates the NF-κB pathway, were detected as were t(14;17) rearrangements involvingNIK in 2% of MM samples. Activation of kinases in myeloma through rearrangements presents an opportunity to use treatments existing in other cancers.